2018
DOI: 10.3892/mmr.2018.9350
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Sirt3 aggravates cisplatin nephrotoxicity via enhanced renal tubular apoptosis and inflammation

Abstract: Cisplatin-based chemotherapy is commonly used in the treatment of solid tumors; however, this agent is limited by its adverse effects on normal tissues, including the kidneys, ears and peripheral nerves. Mechanisms of cisplatin nephrotoxicity are proposed to involve oxidative stress, inflammation, cellular apoptosis and cell cycle regulation. Sirtuin 3 (Sirt3) is a member of the sirtuin family of NAD+-dependent enzymes with homology to Saccharomyces cerevisiae gene silent information regulator 2. Sirt3 is loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Another study reported that SIRT3 could diminish inflammation and mitigated endotoxin‐induced acute lung injury (ALI), suggesting that the induction/activation of SIRT3 may serve as a new therapeutic strategy in ALI. Besides, SIRT3 deficiency aggravated cisplatin‐induced nephrotoxicity mainly by increasing renal inflammation . The current study showed that SIRT3 expression was increased by celastrol treatment in liver fibrosis, showing that SIRT3 is essential for the liver protection effect of celastrol against liver fibrosis.…”
Section: Discussionmentioning
confidence: 51%
“…Another study reported that SIRT3 could diminish inflammation and mitigated endotoxin‐induced acute lung injury (ALI), suggesting that the induction/activation of SIRT3 may serve as a new therapeutic strategy in ALI. Besides, SIRT3 deficiency aggravated cisplatin‐induced nephrotoxicity mainly by increasing renal inflammation . The current study showed that SIRT3 expression was increased by celastrol treatment in liver fibrosis, showing that SIRT3 is essential for the liver protection effect of celastrol against liver fibrosis.…”
Section: Discussionmentioning
confidence: 51%
“…SIRT3 has been reported to have a protective effect against cardiac hypertrophy and interstitial fibrosis by augmenting antioxidant defense mechanisms [15]. We also reported that the absence of SIRT3 enhances cisplatin-induced renal inflammation and tubular apoptosis [16]. In aged mice, the SIRT3/TGF-β1 interaction plays an important role in the pathophysiology of pulmonary fibrosis [17].…”
Section: Introductionmentioning
confidence: 84%
“…The block was cut into 5 µm sections and stained with periodic acid-Schiff stain (PAS) and Masson's trichrome. Immunohistochemical staining was performed as described previously [16,25,38]. Tissue sections were deparaffinized with xylene, rehydrated through graded washes of ethanol in water, and rinsed in pure water.…”
Section: Histologic Examinationmentioning
confidence: 99%
“…SIRT3 can also protect against sepsis-induced AKI by promoting autophagy via upregulating p-AMPK and downregulating phosphor-mammalian target of rapamycin (p-mTOR) ( Zhao et al, 2018 ). SIRT3 deficiency can increase renal tubular apoptosis and inflammation and aggravate renal injury ( Kim et al, 2018 ). Recent studies suggest that SIRT3 may regulate fatty acid oxidation (FAO) by deacetylating liver kinase B1 and activating AMP-activated protein kinase to reduce cisplatin-induced AKI in mice ( Li et al, 2020 ).…”
Section: Class III Histone Deacetylases and Acute Kidney Injurymentioning
confidence: 99%